اِستثمارُ القراءاتِ القرآنيَّة في تخصُّص اللُّغة العربيَّة والدِّراسات القرآنيَّة - ملامحُ تجربةٍ ميدانيَّة - حذيق العيد (University Of Eloued جامعة الوادي, 2024)
هذه المُداخلة بعنوان: استثمار القراءات القرآنيَّة في تخصُّص اللُّغة العربيَّة والدِّراسات القرآنيَّة - ملامحُ تجربةٍ ميدانيَّة -. وهي تُجيبُ عن سؤال: ما هي الموادُّ الَّتي يُمكِنُ تفعيلُ استثمارِ القراءات القرآنيَّة فيها من بين المُقَرَّراتِ الجامعيَّة، المُوجَّهة لطلبةِ هذا التَّخَصُّصِ؟ وما حُدودُ هذا الاِستثمار؟ وللإجابةِ عن هذا السؤال؛ بنيتُ البحث على الخطةِ الآتيةِ: مُقدِّمةٍ، وثلاثةِ مطالبَ، وخاتمةٍ. أمَّا المقدِّمةُ؛ ففيها تمهيدٌ بمسألتينِ اثنتين: الأولى: العلاقة بين القراءات واللغة العربية، والأخرى: التعريف بتخصص اللغة العربيَّة والدراسات القُرآنية. وأمَّا المطلبُ الأوَّل: موادُّ طور الليسانس؛ ففيه أتناول مادَّتين من الموادِّ التي تم تدريسها لطلبة السنة ثالثة ليسانس لغة عربية ودراسات قرآنية، واستثمرتُ في تدريسها تنوع القراءات القرآنية، وهما مادتا: الإعجاز القرآني، وأثر القراءات القرآنية في العلوم الشرعية واللغوية. وأمَّا المطلب الثاني: موادُّ طور الماستر؛ فأذكر فيه أيضًا مادَّتين هما: علم توجيه القراءات، والتفسير اللغوي للقرآن الكريم. وأمَّا المطلب الثَّالث: استثمار جديدٌ؛ ففيه اقتراح استحداث مادة جديدة باسم: تناسبُ المعاني المَجنِيَّة من تعدُّد القراءات القُرآنيَّة. وأمَّا الخاتمةُ؛ ففيها رصدٌ للنَّتائج المُتَوَصِّلِ إليها، والتي مِن أهمِّها: أنَّ هُناك تكاملاً معرفيًّا كبيرًا بين القراءات وعلوم اللغة العربيَّة من جهة الإمداد والاِستمداد، وأنه – في علوم اللغة العربية -، لا ينبغي إهمال الاستفادة من القراءات جميعها متواترها وشاذِّها. Abstract: This intervention entitled "Investing in Quranic readings within the Arabic language and Quranic studies Major - Features of a field experiment -" aims to answer the question of what subjects that can make use of investing in the Qur’anic readings among university courses directed at students of this major and what are the limits of this investment. To answer this question, this research follows a plan of an introduction, three chapters, and a conclusion. The introduction provides a preliminary initiation to the research subject by addressing two issues. The first is the relationship between the readings and the Arabic language, while the second is the introduction of the Arabic language and Quranic studies major. In the first chapter-Bachelor’s degree subjects-, I address two of the subjects taught to Bachelor third-year students of the Arabic Language and Quranic Studies major, and I invested the diversity of the Qur’anic readings in teaching these two subjects namely: "the Quranic inimitability" and "the impact of Qur’anic readings on the jurisprudence and linguistic sciences". Likewise, in the second chapter –Master's degree subjects-, I address two subjects: the science of directing readings, and the linguistic interpretation of the Holy Qur’an. In the third chapter - A new investment-, I propose the introduction of a new material called: the proportionality of the derived meaning from the multiple readings of the Qur’an. The conclusion summarizes the research findings, most importantly that there is a great cognitive complementarity between the readings and the sciences of the Arabic language in terms of supply and derivation, and that - in the sciences of the Arabic language - benefiting from all the readings, whether it be continuously transmitted readings or irregular ones, should not be neglected.
Intervention
Keywords: القراءات القرآنية; استثمار; تخصص اللغة العربية; الدراسات القرآنية; Quranic readings; Investing; Arabic language and Quranic studies Major